A new and endemic species of Struthanthus (Loranthaceae) from Guerrero, Mexico - María Guadalupe Maldonado-Borja; Rosa Cerros-Tlatilpa (Plant Ecology and Evolution)
Background and aims – Struthanthus is a neotropical genus with 60 to 70 species, distributed from northern Mexico to Argentina. Eighteen species are reported in Mexico. During fieldwork to investigate Struthanthus in Mexico, a new species was collected in the state of Guerrero. We present a full description, distribution map, illustrations, and photographs of an unusual new Struthanthus species endemic to Guerrero, Mexico. Material and methods – This study is based on fieldwork, literature revision, and examination of herbarium material. Collected specimens were prepared for storage in the herbarium, analysed, measured, described, and photographed. Preliminary conservation assessment is based on spatial analyses following IUCN guidelines and criteria. Key results – We propose a new species of Struthanthus for Guerrero, Mexico, S. longipetiolatus. This species is only known from cloud forests, oak-pine forests, and oak forests in the province of Sierra Madre del Sur, in the state of Guerrero. A distribution map and an identification key are provided for S. longipetiolatus and its morphologically similar congeners in the region. Conclusion – The newly described species increases the number of Struthanthus species in Mexico to 19 and the number of endemic species to nine. This discovery underlines the need for continued botanical inventories and research on parasitic plants.